2010
DOI: 10.1016/j.atmosenv.2010.09.016
|View full text |Cite
|
Sign up to set email alerts
|

New Directions: Need for better understanding of plastic waste burning as inferred from high abundance of terephthalic acid in South Asian aerosols

Abstract: Terephthalic acid (1,4-benzenedicarboxylic acid; t-Ph) is an important industrial material used for making plastics such as polyester fibre and PET (polyethyleneterephthalate) thermoplastics. In term of public health, t-Ph promotes a bladder cancer (Heck and Tyl, 1985).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 11 publications
3
34
3
Order By: Relevance
“…We found that concentration of tPh acid in PM 2.5 is similar to that reported from Sapporo (mean: 2.6 ng m −3 , Aggarwal and Kawamura, 2008) but is lower than those from Chennai (mean: 52 ng m −3 , Pavuruli et al, 2010) and Nainital (mean: 4.3 ng m −3 , Hegde and Kawamura, 2012). tPh could be produced from open burning of solid waste (plastic) (Simoneit et al, 2005;Kawamura and Pavuluri, 2010), which occurs commonly in Tanzania. Concentrations of total ketoacids in Morogoro (mean: 38-54 ng m −3 ) with a predominance of ωC 2 are comparable to those from other sites whereas concentrations of total α-dicarbonyls (mean: 5.7-7.8 ng m −3 ) are lower than those reported in the literature (Table 3).…”
Section: Comparison Of Molecular Composition Of Diacids and Related Csupporting
confidence: 79%
See 2 more Smart Citations
“…We found that concentration of tPh acid in PM 2.5 is similar to that reported from Sapporo (mean: 2.6 ng m −3 , Aggarwal and Kawamura, 2008) but is lower than those from Chennai (mean: 52 ng m −3 , Pavuruli et al, 2010) and Nainital (mean: 4.3 ng m −3 , Hegde and Kawamura, 2012). tPh could be produced from open burning of solid waste (plastic) (Simoneit et al, 2005;Kawamura and Pavuluri, 2010), which occurs commonly in Tanzania. Concentrations of total ketoacids in Morogoro (mean: 38-54 ng m −3 ) with a predominance of ωC 2 are comparable to those from other sites whereas concentrations of total α-dicarbonyls (mean: 5.7-7.8 ng m −3 ) are lower than those reported in the literature (Table 3).…”
Section: Comparison Of Molecular Composition Of Diacids and Related Csupporting
confidence: 79%
“…In Tanzania, dumping of municipal solid waste (large amounts of plastics) into open landfills is very common and 60 % of daily domestic solid waste are disposed and subjected to open burning (Kassim, 2006). Plastic burning under open-fire conditions and local anthropogenic emissions in both seasons should be responsible for these aromatic acids (Yassaa et al, 2001;Simoneit et al, 2005;Kawamura and Pavuluri, 2010).…”
Section: Molecular Composition and Seasonal Variations Of Diacids Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In factor 3, glyoxal and tPh were recognized together, suggesting an important emission from field burning of municipal wastes. Terephthalic acid is extensively produced during the burning of the municipal solid wastes and/or plastic polymers (Simoneit et al, 2005;Kawamura and Pavuluri, 2010) whereas glyoxal is produced during photo-oxidation of p-xylene as it is one of the important raw materials for terephthalic acid dimethyl ester (Volkamer et al, 2001).…”
Section: Principal Component Analysis For Selected Speciesmentioning
confidence: 99%
“…Open burning of municipal solid waste (large amounts of plastics) is very common in Tanzania (Kassim, 2006), together with local anthropogenic emissions. These sources should also be responsible for the aromatic diacid (Yassaa et al, 2001;Simoneit et al, 2005;Kawamura and Pavuluri, 2010).…”
mentioning
confidence: 99%